2015
DOI: 10.1002/cctc.201500293
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous FeN/C Materials with High Catalytic Performance in the Oxygen Reduction Reaction

Abstract: The tedious and costly route of the general nanocasting method hinders the commercial application of mesoporous non‐precious metal catalysts based on transition metal‐coordinating nitrogen‐doped carbons (MN/C). Here, a simple, economic and sustainable hydrothermal carbonization (HTC)/soft templating method is demonstrated for the direct preparation of mesoporous FeN/C materials (FeN/MC). By this method, FeN/MC materials with high specific surface area, hierarchically mesoporous structure, and appropriate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…These authors found enhanced graphitization at lower temperatures caused by the presence of Mo. Finally, several other reports utilize different mixtures of metal, N, and C precursors to give active catalysts. …”
Section: Pyrolyzed Nonprecious Metal Catalystsmentioning
confidence: 95%
“…These authors found enhanced graphitization at lower temperatures caused by the presence of Mo. Finally, several other reports utilize different mixtures of metal, N, and C precursors to give active catalysts. …”
Section: Pyrolyzed Nonprecious Metal Catalystsmentioning
confidence: 95%
“…2 Thus far, a wide range of carbon materials has been used, including carbon nanotubes, 3,4 graphene [5][6][7] and porous carbon, [8][9][10][11][12] where the embedded nitrogen atoms can modify the local electron density of neighboring carbon atoms and facilitate oxygen adsorption and dissociation. 4,13,14 Moreover, addition of transition metals such as Fe and Co [15][16][17][18][19][20] to N-doped carbon can further improve the electrocatalytic performance, as the transition metals may either serve as part of the ORR active sites or assist the formation of the active sites. [21][22][23] Therefore, the selection of appropriate precursors to prepare the catalysts is a critical first step.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have investigated the effect of using a molecular‐based receptor to graft a nitrogenous terpyridine‐based ligand to selectively imprint the most active pyridinic nitrogen groups on the surface [27] . While it has been reported in the literature that a N 3 site might be a defect to the most widely accepted active site, we deliberately formed these sites specifically on the surface to assess the activity of sites that differ from the N 2+2 type site [28–31] . A surface modification approach was adapted to functionalize the surface with the nitrogen and then iron was added to create coordination motifs on the surface [27,32] .…”
Section: Introductionmentioning
confidence: 99%
“…[27] While it has been reported in the literature that a N 3 site might be a defect to the most widely accepted active site, we deliberately formed these sites specifically on the surface to assess the activity of sites that differ from the N 2 + 2 type site. [28][29][30][31] A surface modification approach was adapted to functionalize the surface with the nitrogen and then iron was added to create coordination motifs on the surface. [27,32] Next, we investigated the role that carbon supports played on our novel catalyst design and found that the least porous support (Vulcan XC-72 carbon) yielded the highest activity.…”
Section: Introductionmentioning
confidence: 99%